hey matheamtica community,
im working on a project and i got a problem. I want to perform a logical test in order to check if two expression are the same. my code is the following:
test1 = (2 epsH r[b[t]] - b[t] (1 + r[b[t]])^2)/(
b[t] (-2 epsH + b[t] (1 + r[b[t]])))
test2 = (2*epsH - (((1 + r[b[t]])*(2*epsH - b[t]*(1 + r[b[t]])))))/(b[
t]*(2*epsH - b[t] (1 + r[b[t]])))
test3 = test1 == test2
Expand[test3]
i mean i got the basics of doing logical tests f.e :`
In[86]:= x = 5
Out[86]= 5
In[87]:= x == 7
Out[87]= False
But i read in the documentation about "Equal" that the command "Expand" should do the deal for what i want but appareantly it isnt doing a logical test but rather expanding both expressions. I would be greatful if someone can gibve me a hand and maybe explain me what i misunderstood about the language of mathematica for this case. ty a lot for all answers